2009
DOI: 10.1071/as08014
|View full text |Cite
|
Sign up to set email alerts
|

The Metallicity Distribution of Distant F and G Type Stars in the CFHT Legacy Survey Deep Field

Abstract: Abstract:We study the metal abundances of F and G type stars in the Galactic disk and halo using the CanadaFrance-Hawaii Telescope Legacy Survey D4 field. For a sample of stars within 7 kpc of the Galactic plane, we derive mean abundance values of [Fe/H] = −0.77 ± 0.36 dex for the thick disk, and [Fe/H] = −1.42 ± 0.98 dex for the stellar halo, respectively. These metallicites are consistent with the metallicity estimates from the Sloan Digital Sky Survey Data Release 6. We do not find a vertical abundance grad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…The mean metallicity in interval 5 < r ≤ 8 kpc is about −1.0 and smoothly decreases from −0.6 to −0.8 in interval 2.5 < r ≤ 5 kpc. Our results are consistent with the results of Siegel et al (2009) and Karatas et al (2009). Siegel et al find a monometallic thick disc and halo with abundances of [Fe/H] =−0.8 and −1.4 respectively.…”
Section: Metallicity Distributionsupporting
confidence: 93%
See 2 more Smart Citations
“…The mean metallicity in interval 5 < r ≤ 8 kpc is about −1.0 and smoothly decreases from −0.6 to −0.8 in interval 2.5 < r ≤ 5 kpc. Our results are consistent with the results of Siegel et al (2009) and Karatas et al (2009). Siegel et al find a monometallic thick disc and halo with abundances of [Fe/H] =−0.8 and −1.4 respectively.…”
Section: Metallicity Distributionsupporting
confidence: 93%
“…The mean metallicity in intervals 5 < r 8 kpc is about −1.0 and the mean metallicity smoothly decreases from −0.6 to −0.8 in intervals 2.5 < r 5 kpc. Our results are consistent with the results of Siegel et al (2009) and Karatas et al (2009) As shown in Fig. 5, at larger distance, r > 10 kpc, compared to the typical error bars, the mean metallicity distributions variation with Galactic longitude is almost flat.…”
Section: Metallicity Variation With Galactic Longitudesupporting
confidence: 92%
See 1 more Smart Citation
“…Remarkably, their results would be consistent with the complete absence of a thick disc in the Milky Way or its reduction to the metal‐weak thick disc described by Norris (1987). Karataş et al (2009) have also recently analysed ugriz photometry from the Canada‐France‐Hawaii Telescope Legacy Survey Data Release 4 (CFHTLS DR4). In contrast to other studies, they find a vertical abundance gradient in the halo.…”
Section: Introductionsupporting
confidence: 67%
“…Accurate determination of the properties of the components of the Galaxy requires surveys with sufficient sky coverage to assess the overall geometry (de Jong et al 2010). Most previous investigations about the Galactic metallicity distribution used only one or a few fields along the lines-of-sight (Du et al 2004;Siegel et al 2009;Karatas et al 2009). The fields used in this paper are toward different directions, the Galactic center, the anticentre at median and high latitudes, 20 • < |b| < 60 • .…”
Section: Batc Survey and Data Reductionmentioning
confidence: 99%